Ebola Virus Infection - İlkay BOZKURT (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2014)
Ebola virus is one of the cause of viral hemorrhagic fever with high mortality rate. This recent West African outbreak is the largest Ebola outbreak in history. The current Ebola outbreak is caused by Zaire Ebola virus species. Ebola virus disease can be transmitted by direct contact with blood, body fluids and skin of infected patient and also person who have died because of the disease. The clinical manifestations of infection are nonspecific so it is important to consider differential diagnosis including infectious and non-infectious disorders during the evaluation of the disease. There are no approved antiviral therapy and also vaccine yet but early results of ongoing researches looks promising. The progression of the illness is considerably related to effective supportive therapy.